Starving the Stress Gremlin : a Cognitive Behavioural Therapy Workbook on Stress Management for Young People. - Collins-Donnelly, Kate (Jessica Kingsley Publishers, 2013)
Drawing on cognitive behavioural therapy principles, this book is a valuable resource for helping children and young people understand and control their stress. It uses example scenarios, activities and young people's comments to teach them effective emotional management skills and is aimed at those working with young people as well as parents.